Two genes encode highly similar chloroplastic NADP-malic enzymes in Flaveria. Implications for the evolution of C4 photosynthesis. - Marshall, J S (1996)
To gain an understanding of the molecular events underlying the evolution of C4 photosynthesis, we have undertaken as detailed study of the NADP-malic enzyme gene family in C4 and C3 species of Flaveria. Three genomic clones form the C4 species Flaveria bidentis were characterized and found to encode two highly similar chloroplastic forms of NADP-malic enzyme, termed ME1 and ME2. Genomic southern blotting with gene-specific probes showed that both Me1 and Me2 are found in Flaveria trinervia (C4) and Flaveria pringlei (C3) as well as in F. bidentis. Northern blots demonstrated that Me1 expression in leaves parallels the degree of C4 photosynthesis in seven Flaveria species. Furthermore, whereas Me2 was expressed at a low level in both roots and leaves of F. bidentis, Me1 expression was seen only in leaves and was light-regulated. We discuss these results in the context of the evolution of C4 photosynthesis in Flaveria.